Preparation of 304 Stainless Steel Powder for 3D Printing by Vacuum-Induced Multistage Atomization - Jiang, Xueyu; Che, Xin; Tian, Chen; Zhu, Xiaofei; Zhou, Ge; Chen, Lijia; Li, Jianlin (Frontiers in Materials, 2021)
A vacuum-induced multi-stage atomization process was adopted to fabricate the high-performance 304 stainless steel powder for 3D printing, based on the flexible control of the droplet spheroidization and solidification process. The 36.7 μm-median diameter (D50) 304 stainless steel powder with high sphericity was successfully obtained, together with particle size proportion of 45-55 μm larger than 35% and the lower oxygen and nitrogen content increment below 0.04%.